2013
DOI: 10.1371/journal.pone.0085158
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Increase in Oxidative Stress in Carbon-Irradiated Normal Human Skin Fibroblasts

Abstract: Skin complications were recently reported after carbon-ion (C-ion) radiation therapy. Oxidative stress is considered an important pathway in the appearance of late skin reactions. We evaluated oxidative stress in normal human skin fibroblasts after carbon-ion vs. X-ray irradiation. Survival curves and radiobiological parameters were calculated. DNA damage was quantified, as were lipid peroxidation (LPO), protein carbonylation and antioxidant enzyme activities. Reduced and oxidized glutathione ratios (GSH/GSSG)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 20 publications
1
30
1
Order By: Relevance
“…Moreover, a putative interindividual variability in radiosensitivity between human cell donors could explain in part such a discrepancy between studies. The RBE (D 10 ) calculated from our data (2.6) was rather smaller than that found with normal human fibroblasts (3.29) in our laboratory using the same irradiation facility (30). However, it was in the range of a previously published database consisting in 855 in vitro survival experiments after ion and photon irradiation (31).…”
Section: Discussioncontrasting
confidence: 64%
“…Moreover, a putative interindividual variability in radiosensitivity between human cell donors could explain in part such a discrepancy between studies. The RBE (D 10 ) calculated from our data (2.6) was rather smaller than that found with normal human fibroblasts (3.29) in our laboratory using the same irradiation facility (30). However, it was in the range of a previously published database consisting in 855 in vitro survival experiments after ion and photon irradiation (31).…”
Section: Discussioncontrasting
confidence: 64%
“…In particular, Yanagi et al (2010) reported severe acute and late skin complications on patients treated for unresectable bone and soft tissue sarcoma by a C-ion dose escalation protocol. We have recently reported that skin fibroblasts showed a stronger increase in oxidative stress after C-ion vs Xray irradiation, even at late times -two weeks -after in vitro irradiation (Laurent et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Alkaline comet assay was performed as described by Laurent et al 50 Comet images were taken using a confocal microscope (Olympus FV1000). Images were analyzed using the computer image analysis software Casp to obtained the Olive Tail Moment (OTM).…”
Section: Alkaline Comet Assaymentioning
confidence: 99%